An Integrative Analysis of Transcriptome and GWAS Data to Identify Potential Candidate Genes Influencing Meat Quality Traits in Pigs - Liu, Xianxian; Zhang, Junjie; Xiong, Xinwei; Chen, Congying; Xing, Yuyun; Duan, Yanyu; Xiao, Shijun; Yang, Bin; Ma, Junwu (Frontiers in Genetics, 2021)
Understanding the genetic factors behind meat quality traits is of great significance to animal breeding and production. We previously have conducted a genome-wide association study (GWAS) for meat quality traits in a White Duroc × Erhualian F2 pig population using Illumina porcine 60K SNP data. Here, we further investigate the functional candidate genes and their network modules associated with meat quality traits by integrating transcriptomics and GWAS information. Quantitative trait transcript (QTT) analysis, gene expression QTL (eQTL) mapping and weighted gene co-expression network analysis (WGCNA) were performed using the digital gene expression (DGE) data from 493 F2 pigs’ muscle and liver samples. Among the quantified 20108 liver and 23728 muscle transcripts, 535 liver and 1014 muscle QTTs corresponding to 416 and 721 genes, respectively, were found to be significantly (P < 5 × 10-4) correlated with 22 meat quality traits measured on longissiums dorsi muscle (LM) or semimembranosus muscle (SM). Transcripts associated with muscle glycolytic potential (GP) and pH values were enriched for genes involved in metabolic process. There were 42 QTTs (for 32 genes) shared by liver and muscle tissues, of which 10 QTTs represent GP- and/or pH-related genes, such as JUNB, ATF3 and PPP1R3B. Furthermore, a genome-wide eQTL mapping revealed a total of 3054 eQTLs for all annotated transcripts in muscle (P < 2.08 × 10-5), including 1283 cis-eQTLs and 1771 trans-eQTLs. In addition, WGCNA identified 5 modules relevant to glycogen metabolism pathway and highlighted the connections between variations in meat quality traits and genes involved in energy process. Integrative analysis of GWAS loci, eQTL and QTT demonstrated GALNT15/GALNTL2 and HTATIP2 as strong candidate genes for drip loss and pH drop from postmortem 45 min to 24 h, respectively. Our findings provide valuable insights into the genetic basis of meat quality traits and greatly expand the number of candidate genes that may be valuable for future functional analysis and genetic improvement of meat quality.